Echoes between us - McGarry, Katie (Tor Teen, 2020)
In a novel told in two voices, Veronica and Sawyer become partners for their senior project and soon they are helping each other battle the ghosts that haunt them--her illness causing blinding migraines and his adrenaline addiction.